Pengembangan E-Bahan Ajar untuk Melatih Kemampuan Berfikir Kausalitas pada Siswa SMA N 8 Padang - Hari Guna Sanjaya; Rahmiyati Rahmiyati (YASIN, 2026)
This study was motivated by students’ low causal thinking skills in history learning and the limited availability of e-teaching materials specifically designed to train these skills. The study aimed to develop e-teaching materials based on the Indonesian Independence Proclamation content to train the causal thinking ability of students at SMAN 8 Padang. The research employed a Research and Development (R&D) method using the ADDIE model, which comprised analysis, design, development, implementation, and evaluation. The research subjects included two material expert lecturers, two teaching-material expert lecturers, one history teacher, and 36 eleventh-grade students; data were collected using validation sheets and analyzed through qualitative and quantitative approaches. The results showed that the development procedure encompassed needs analysis, structural and content design, product development through expert validation, classroom implementation, and an evaluation of effectiveness. The feasibility of the e-teaching materials was categorized as very feasible, with mean ratings of 3.35 from material experts and 3.2 from teaching-material experts, while practicality as assessed by the teacher and students was also categorized as very practical, with mean ratings of 3.9 and 3.55, respectively. The effectiveness of the e-teaching materials was reflected in students’ causal thinking achievement of 87.44%, categorized as very good. The study concludes that the e-teaching materials on the Indonesian Independence Proclamation are very feasible, very practical, and effective for training learners’ causal thinking skills in history learning, and they contribute to the development of more meaningful history learning media oriented toward higher-order thinking skills.